Revolutionising the document workflow using blockchain in banking sector - Ervin Domazet; Merdzan, Gunter; Cvetkoska, Violeta; Daniela Mechkaroska; Serdar Serdaroglu; Bilal Sucubasi (University of Nis, 2024)
Blockchain is a distributed ledger technology that can revolutionise the banking sector by increasing transparency, reducing costs, and enhancing security. However, the success of any banking service lies in the efficiency of serving it, which depends on the smoothness of internal documents and process flows. This paper proposes a novel method that uses blockchain infrastructure to address the efficiency, security, and privacy of workflow processes in the banking sector. Our approach combines Alfresco DMS and CMIS with the orchestration tool Camunda for workflow management and secures them with a notary using the Factom Blockchain. This method provides a secure, efficient, and reliable way for banks to process transactions, store documents, and manage their processes. It will enable banks to process transactions faster, reduce costs, minimise the risk of fraud, increase customer satisfaction, and fully consider blockchain technology's advantages.
Keywords: document management; workflow; automation; process management; blockchain; banking